Transformasi Organisasi dalam Administrasi Publik: Meningkatkan Efisiensi dan Responsivitas - Badi, Salehan; Herman, Herman; Idolawati, Idolawati; Ananda, Dhea (Perkumpulan Dosen Muda (PDM) Bengkulu, 2021)
In an era of ever-changing dynamics, public administration is faced with pressure to continuously improve efficiency and responsiveness in providing services to the public. Organizational transformation has become a crucial strategy in achieving this goal. This article discusses the role of organizational transformation in the context of public administration, focusing on efforts to improve efficiency in bureaucratic processes as well as responsiveness to public needs. In this article, we will describe various methods and strategies that can be used by government agencies to achieve this goal, as well as discuss the challenges that may be faced in the proces